Environmentally Friendly Rice Farmer Empowerment for Sustainable Food Security in Banten Province - Asih Mulyaningsih; Suherna Suherna; Gugun Gunawan (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluh Pertanian Indonesia), 2021)
Empowerment is a key factor in accentuating the role of farmer communities as the main actors in managing the cultivation of Indonesian staple food, that is, rice. This study was intended to analyze the factors influencing the empowerment of farmers to manage environmentally friendly lowland rice production for sustainable agricultural development in Banten Province. With a descriptive design, this research collected data through a questionnaire survey involving 180 respondents, sampled from a predefined population of rice farmers. It was carried out in three regencies in the province, namely Serang, Pandeglang, and Lebak, for three months from April to June 2019. The data were analyzed using statistical inference, SEM, in LISREL 8.73 (Linear Structural Relationships). The results showed that the empowerment of lowland rice farmers to adopt eco-friendly innovation was determined by individual characteristics (i.e., non-formal and formal educational attainment and cosmopolitanism) and the existence of encouragement to implement the innovation (i.e., support from farmer community, market support, and technological information support). In conclusion, to increase the empowerment of rice farmers in the scheme of sustainable food security, farmers, government, and other relevant parties need to pay attention to the characteristics of innovation users and promote the adoption of eco-friendly practices in lowland rice cultivation.